Political Participation of Legislative Election Voters in Bengkulu City: Political Participation of Legislative Election Voters in Bengkulu City - Hidayana, Rizki Apriva (International Journal of Humanities, Law, and Politics, 2023)
General elections for the legislature are significant junctures in the political process because they involve the community in choosing its legislators. The city of Bengkulu held engaging legislative elections between 2014 and 2019, which are worth studying and analysing in the perspective of civic engagement. Both qualitative and quantitative research methodologies were used in this study. The political engagement of the electorate in the legislative elections in Bengkulu City saw numerous dynamics and changes between 2014 and 2019. Political campaigns run by legislative candidates can also have an impact on levels of political involvement. If the campaign fails to inspire and influence the electorate to vote in the 2019 election, political engagement may decline. Analysing political involvement is crucial for evaluating Bengkulu City's level of democracy and political representation. The degree of public confidence in the political process and candidates for public office is demonstrated by the amount of political involvement. The public's apathy and discontent with the political system may also be raised by poor political involvement.